Hadith #2198 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin al-Fadl 'Aram محمد بن الفضل السدوسي أبو النعمان عارم; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Abu Dawud said “The opinion of Ibn ‘Abbas has been mentioned in the following tradition. “Ahmad bin Salih and Muhammad bin Yahya narrated this is the version of Ahmad (bin Salih)” from ‘Abd Ar Razzaq from Ma’mar from Al Zuhri from Abu Salamah din Abd Al Rahman bin ‘Awf and Muhammad bin ‘Abd Al Rahman bin Thawban from Muhammad bin Iyas that Ibn ‘Abbas, Abu Hurairah and ‘Abd Alah bin ‘Amr bin Al ‘As were asked about a virgin who is divorced three times by her husband. They
Grade: Sahih

Hadith #2219 - Sunan Abi Dawud - Hammad bin Salama حماد بن سلمة; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin 'Urwa هشام بن عروة; Muhammad bin al-Fadl 'Aram محمد بن الفضل السدوسي أبو النعمان عارم; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
Khawlah was the wife of Aws ibn as-Samit; he was a man immensely given to sexual intercourse. When his desire for intercourse was intensified, he made his wife like his mother’s back. So Allah, the Exalted, sent down Qur’anic verses relating to expiation for zihar.
Grade: Sahih

Hadith #4993 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ali bin Abd al-A'la علي بن عبد الأعلى; Ibrahim bin Tahman إبراهيم بن طهمان; Muhammad bin al-Fadl 'Aram محمد بن الفضل السدوسي أبو النعمان عارم; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Zayd bin Arqam (Sunan Abi Dawud)
The Prophet (ﷺ) said: To harbour good thoughts is a part of well-conducted worship. (This is according to Nasr’s version). Abu Dawud said: Mahna’ is reliable and he is from Basrah.
Grade: Hasan